Mempersiapkan Generasi Unggul melalui Motivasi dan Pembekalan Pendidikan bagi Peserta Didik TPQ At-Tawwabin - Sucayono; Soeyatno, Rahmah Farahdita (Abdimisi, 2025)
The quality of future generations is greatly influenced by motivation and educational preparation from an early age, including in non-formal educational settings such as Taman Pendidikan Al-Qur’an (TPQ). TPQ At-Tawwabin, as a partner in this community service program, holds great potential in shaping a generation that excels both spiritually and intellectually. However, it faces challenges such as low learning motivation among students, lack of varied teaching methods, and limited character development guidance. This community service activity aims to provide motivation and educational enrichment to the students of TPQ At-Tawwabin to foster enthusiasm for learning, religious character, and a positive vision for the future. The methods employed included an educative-participatory approach through motivational seminars, basic skills training, educational games, and mentoring sessions. The results showed increased enthusiasm and active participation in learning activities, improved understanding of the importance of education, and a growing sense of self-awareness regarding their goals and future roles. In conclusion, this program effectively enhanced the motivation and educational development of TPQ At-Tawwabin’s students. It is recommended that similar activities be conducted continuously and involve active participation from parents and educators to achieve optimal results. Keywords: community service, learning motivation, TPQ, character education, excellent generation.